Characterization of Vibrio Parahaemolyticus Isolated From Local Cockles (Anadara Granosa) From Tanjung Karang, Kuala Selangor - Bilung, Lesley Maurice (2006)
Vibrio parahaemolyticus is widespread in occurrence and has been recognized as a cause of gastroenteritis related to consumption of raw or improperly cooked seafood. Outbreaks of V. parahaemolyticus food poisoning are most common in Taiwan, Japan and Southeast Asia. In this study, V. parahaemolyticus was isolated from 62 of 100 (62%) samples of cockles (Anadara granosa) collected from Tanjong Karang, Kuala Selangor. A total of 62 strains were studied for the presence or absence of regulatory gene (toxR), virulence genes (tdh and trh), their antibiotic resistance, the occurrence of plasmids and their molecular fingerprints by Randomly Amplified Polymorphic DNA – Polymerase Chain Reaction (RAPD-PCR) and Enterobacterial Repetitive Intergenic Consensus - Polymerase Chain Reaction (ERIC-PCR) assays. All 62 strains were positive for the regulatory gene (toxR) of V. parahaemolyticus. The PCR analysis for the detection of tdh or trh genes showed two (3.2%) positive strains carrying tdh gene and eleven (17.7%) strains had trh gene. The MPN value for all samples was more than 1100 MPN/g. This study has shown that all strains were multiple resistant to three or more of the seventeen antibiotics tested with the MAR indices ranging from 0.58-0.94. All isolates of V. parahaemolyticus were highly resistant towards the antibiotics tested, except one strain that was sensitive towards norfloxacin. Plasmids were found in 80% of the strains analyzed and 18 different plasmid profiles were observed. The plasmid size ranged from 2.7 to more than 54 kb. Two molecular typing methods were used in this study to examine the genetic relatedness among the V. parahaemolyticus strains. In the analysis by RAPD-PCR and ERIC-PCR, the size of RAPD and ERIC fragments ranged from 0.25 to 10.0 kb with an average number of ten and eight bands, respectively. Sixty-two genotypes among the 62 V. parahaemolyticus strains were generated using RAPD and ERIC-PCR which indicates that the strains were very diverse. Hence, this study, demonstrated that the local cockles are potential source for pathogenic V. parahaemolyticus.